Utilizing infrared thermography to predict pork quality - T E Lawrence; M F Spire; Michael E Dikeman; Melvin C Hunt; S B Hogge; B W James (Kansas Agricultural Experiment Station Research Reports, 2001)
Three experiments using 63 pigs were conducted to determine if infrared thermography could segregate pigs based on subsequent pork quality. Pigs were subjectively classified as either "hot" or "normal" based on infrared surface temperature of the loin region prior to slaughter. In the first experiment 18 market weight pigs were transported, imaged by infrared thermography and slaughtered immediately after 1 to 4 h of lairage. Differences in meat quality were detected; hot pigs had lower a* (less red) and chroma (less intense red color) values, and higher hue angle (less red/more yellow) values, all of which indicate paler muscle color. In the second experiment, 27 market weight pigs were transported, held in lairage for 12 to 16 h, imaged by infrared thermography, and then slaughtered. In the third experiment, 18 market weight pigs were transported, imaged by infrared thermography, held in lairage for 12 to 16 h, and then slaughtered. Regardless of the time infrared images were taken, no meat quality differences between hot and normal pigs were detected when pigs were held in lairage for 12 to 16 h. These data suggest that measurement of live animal surface temperature by infrared thermography may allow for detection of poor meat quality if pigs are slaughtered without extended lairage.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Infrared thermography; Pork quality